Hereditary Haemoglobin Disorders of Anaemic Patients Attending in a Rural Tertiary Level Hospital (KYAMC Journal, 2017)
Background: Regularly patients attending in the hospital with severe illness for medical treatment. A large number of patients came with features of anaemia. Many of them show hereditary haemoglobin disorders.Objective: This study was done to find out the pattern of hereditary haemoglobin disorders of anaemic patients attending in the hospital for medical treatment in a tertiary level rural hospital.Method: This descriptive type of retrospective study was performed with 151 cases of anaemic patients whose whole blood show abnormality in haemolobin on capillary haemoglobin electrophoresis. Haemoglobin as well as haematocrit and red blood cells indices were performed by using fully automated haematology lab automation (Sysmex XN-1000). Then haemoglobin electrophoresis was performed to see haemoglobin disorder by using Capillary-2 Haemoglobin Electrophoresis, Sebia, France.Results: All of the 151 cases of hereditary haemoglobin disorders were categorized into four groups. Of those Haemoglobin-E ß thalassaemia was 64.90%, ß thalassaemia minor was 17.22%, Haemoglobin-E haemoglobinopathies was 11.92% and ß thalassaemia major was 5.96% of cases. Among 151 patients; 106 (70.20%) patients were severely anaemic, 30 (19.87%) patients were moderately anaemic and 15 (9.93%) patients were mildly anaemic. Among 98 patients of haemoglobin-E ß thalassaemia, 87 (88.76%) patients were severely anaemic.Conclusion: All anaemic patients especially who suffers from anaemia for a long period of time should be checked for haemoglobin disorders by routine haematological investigation and peripheral blood film examination. The patients with persistent anaemia and whose blood shows hypochromic microcytic anaemia should be advised for haemoglobin electrophoresis.KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 545-549